Strategie zur Maximierung des Endvermögens bei Meidung des Ruins - Ein geeigneter Ansatz bei Anlagen zur Alterssicherung? - Hellmut D. Scholtz (Die Rentenversicherung, 2003)
Es werden im Folgenden für eine Abfolge von rentabel eingeschätzten Investments Komponenten und Lösungswege zur Maximierung des Endvermögens bei Ausschluss des Ruins aufgezeigt. – – The appoach points out the components of optimum strategies for maximizing yields while avoiding ruin. Provided all decisions are defined as elements of a decision process, the final capital can only be maximized if the ratio of possibke gains and losses is greater than a fixed cut-off point and if a defined fraction of the capital is invested.
Keywords: G32; C73; 330; Risiko; Investmenttheorie; Entscheidungstheorie; Risiko; Entscheidungstheorie; Investitionsentscheidung